ANALISIS KUALITAS LAYANAN TERHADAP TINGKAT KEPUASAN PENGHUNI RUSUNAWA JATINEGARA BARAT - Sihombing, Tretnis; Panjaitan, Robert P.; Tobing, Emerald G.M. (Universitas Kristen Indonesia, 2016)
The purpose of this study was to determine the factors that influence occupant satisfaction Rusunawa and analyze things Occupants required to meet their satisfaction with services provided by the manager. Respondents were selected using purposive sampling method. Total population of 517 families, while respondents consisted of 84 households. Data were analyzed by using Importance Performance Analysis (IPA) and the Cartesian diagram. This study was analyzed by using 19 attributes are available on the five dimensions of service quality that is Tangibles, Reliability, Responsiveness, Assurance and Empathy. Partial results showed there is significant influence between the quality of service to satisfaction of Occupants Rusunawa Jatinegara Barat and attributes are mapped to the most Cartesian diagram is in quadrant II, which means the quality of service Rusunawa studied showed quite good.Keywords: quality of service, satisfaction.